Heterogeneity of epithelial-mesenchymal transition and CD26 expression in hypertrophic scars and keloids - GONG Wanru; LIU Mengchang; LIU Xingke; XIE Defu; YAN Hong (陆军军医大学学报, 2022)
Objective To investigate the histological differences and expression of E-cadherin, Vimentin, matrix metalloprotein-9 (MMP-9), TNF-α, dipeptidyl-peptidase 4 (DPP4, also called CD26) in the margin and center of hypertrophic scar, superficial dilated keloid and normal skin. Methods Ten patients with keloid and another 10 with hypertrophic scar undergoing excision surgery in our hospital from October 2020 to August 2021 were included, and 8 cases requiring partial normal skin resection were also recruited. The resected tissues were collected, the tissue morphology was observed with HE staining, and the expression levels of E-cadherin, Vimentin, MMP-9, TNF-α and CD26 were detected by immunohistochemical staining and Western blotting. Results The E-cadherin expression in the epidermis of both keloid and hypertrophic scar was significantly lower than that of normal skin (P < 0.05), and the level in the edge of keloid was obviously weakened as compared with that of the center (P < 0.05), but there was no significant difference between the edge of hypertrophic scar and the center (P>0.05). By contrast, the expression levels of Vimentin, MMP-9, TNF-α and CD26 in the epidermis of both keloid and hypertrophic scar were remarkably enhanced when compared with those of normal skin (P < 0.05), and the keloids' edge higher than the center (P < 0.05), while no significance between the hypertrophic scars' edge and center (P>0.05). Conclusion The differences in epithelial-to-mesenchymal transition (EMT) and expression of relevant biomarkers within individual scars may be one of the reasons for the diversity of clinical features between hypertrophic scar and keloid, in which TNF-α and CD26 may be the key factors.